HUMAN RESOURCES MANAGEMENT AUDIT TO ASSESS THE EFFECTIVENESS OF EMPLOYEE PERFORMANCE AT PT. KIMIA FARMA TRADING AND DISTRIBUTION (SIDOARJO BRANCH) - JB Amiranto; Sigit Santoso (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
The research objective to be achieved in accordance with the formulation of the problem that has been described is to determine the effectiveness of employees in HR management audits at PT. Kimia Farma Trading & Distribution (Sidoarjo Branch). This study took respondents from several employees with a total of 30 people. In its implementation in the field, this study took primary data using a questionnaire. Secondary data obtained from the administrative supervisor of PT. Kimia Farma Sidoarjo Branch Trading and Distribution includes company profile, company organizational structure and PT. Kimia Farma Trading and Distribution Sidoarjo branch. This type of research uses qualitative research methods. The analytical method used is to set criteria, describe conditions, find causes, and conclude results. In Key analysis that PT. Kimia Farma Trading and Distribution Sidoarjo branch has been running effectively in accordance with company regulations.